ANALISIS KERETAKAN PAVING BLOCK DI PT. SINAR BALI BINA KARYA MENGGUNAKAN FISHBONE - Ismi Mashabai; Silvia Firda Utami; mira sugala (JURNAL INDUSTRI DAN TEKNOLOGI SAMAWA, 2023)
PT. Sinar Bali Bina Karya is a private company engaged in construction and manufacturing. The newly developed division is the Paving Division, which produces Paving Blocks but there are as many as 720 pieces of defects such as cracks, breaks and breaks. Crack defects are among the highest at 337 or as much as 4.21% during the production process. The problem that can occur if this is allowed to continue is the decrease in the level of production productivity which causes losses to the company as much as 9% of the total production of 8000. This problem requires action to be repaired on crack damage using a fishbone diagram. Fishbone diagram can analyze what are the factors that cause damage to the product. There are 5 factors that cause cracks, and the root of the problem lies in the material factor, namely the sand used by mountain sand so that the quality of the sand is very low, then the mixed material will cause the sand to be dissimilar, lack of water can cause the Paving Block dough to become very hard so that it cracks easily. Based on the results of the crack analysis, it can be minimized by selecting good quality materials (sand) to be used for the Paving Block production process.